The More You Know … The More You Enjoy? Applying 'Consumption Capital Theory' To Motion Picture Franchises. Issue 4 (1st October 2016) - Opitz, Christian; Hofmann, Kay H.
ABSTRACT: In this article, we build on Stigler and Becker's (1977) "consumption capital theory" and propose a novel conceptualization of film quality for the analysis of motion picture franchises. Generally, this theory predicts that the utility consumers derive from a particular good or service increases with prior consumption. We test our theoretical conjectures by drawing on the population of sequels that were running in the US between 1992 and 2011. The empirical results point to the explanatory power of the proposed framework. Film executives may use our findings to improve the profitability of their sequel productions. From a theoretical point of view, consumption capital theory allows for a more refined analysis of sequel performance along different dimensions. Moreover, it may provide a fruitful basis for the analysis of other serial media content, including books, TV, music, and games.